(untitled) (BALANCE: JOURNAL OF ISLAMIC ACCOUNTING, 2025)
The Javanese community, which is the majority in Kediri, has unique and profound cultural values that have shaped their way of life, social interactions, and even business practices for generations. Values such as cooperation, empathy, harmony, and deliberation often serve as the foundation for interaction and business management. Based on the explanation above, the urgent research gap is the lack of in-depth understanding of how Javanese cultural values can be specifically and explicitly harmonized in the design and implementation process of accounting information systems in SMEs. This research aims to deeply explore how Javanese cultural values, firmly held MSMEs “Sambal Pecel Bu Siti Kediri”, influence and can be harmonized in the design and implementation of AIS. Javanese cultural values are an important foundation in the life of Javanese society, shaping worldviews, ethics, and daily behavior. This research is a qualitative study based on the philosophy of post-positivism, used to examine objects in their natural conditions. shows that the design and implementation of the AIS in the MSMEs "Sambal Pecel Bu Siti" can be driven by two factors, namely Javanese cultural values and experience. The findings can be explained using the yccy theory, which states that each organization has different ways of operating. The majority of MSMEs actors understand and practice Javanese cultural values such as guyub (cooperation), nrima ing pandum (accepting with sincerity), tepa slira (empathy), and andap ashor (humility). Thus, integrating Javanese cultural values into the design and implementation of the AIS at MSMEs “Sambal Pecel Bu Siti” not only makes operations more efficient but also enhances a sense of ownership and business ethics based on culture. The system that has been built not only serves as a financial control tool but also to preserve noble values in the context of modern business.